Willie Mathieson and the Primary Audience for Traditional Song - McKean, Thomas A. (Tautosakos darbai, 2018)
Focusing on the song notebooks of William Mathieson (1879–1958), a farmworker in North-East Scotland, this essay examines the role of tradition in one man’s life, proposing that people learn, preserve, and perform folklore largely for themselves. Mathieson’s material is preserved as handwritten and typed texts, along with cylinder and tape recordings, made across more than half a century by three collectors: James Madison Carpenter, Hamish Henderson and, crucially, Mathieson himself. I suggest that this depth of evidence can be used in future to elucidate the essential nature of specific examples, but most importantly, I show that the primary audience for tradition is the individual.